(RS)-2-(4-(2-methylpropyl)phenyl)propanoic acid - AJ Ramirez-Cuesta, ISIS (My University, 2017)
Inelastic Neutron Scattering spectrum of (RS)-2-(4-(2-methylpropyl)phenyl)propanoic acid, C₁₃H₁₈O₂, measured on the TOSCA instrument. Ibruprofen.
Keywords: TOSCA